2007
DOI: 10.1007/s10531-007-9233-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the response of open-habitat bird species to landscape changes in Mediterranean mosaics

Abstract: In Mediterranean landscapes, wildfires and land abandonment lead to major landscape modifications primarily by favouring the presence of open, shrub-like habitats. At present, we know very little of how these changes affect patterns of species occurrence at the landscape scale. In this work, we analyse the impact of these landscape changes on the occurrence patterns of eight open-habitat species by using presence/absence data collected in the Catalan Breeding Bird Atlas (NE Spain). We compared the species occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 46 publications
5
36
2
1
Order By: Relevance
“…a given individual will need different types of habitat patches within the landscape to meet its vital needs (Delettre et al 1992). The process of complementation found in the present study is also likely to explain the previously reported preference of Woodlarks for regions with a mix of farmland and shrubland in Spain (Vallecillo et al 2008). …”
Section: Habitat Selection By Mediterranean Woodlarkssupporting
confidence: 65%
“…a given individual will need different types of habitat patches within the landscape to meet its vital needs (Delettre et al 1992). The process of complementation found in the present study is also likely to explain the previously reported preference of Woodlarks for regions with a mix of farmland and shrubland in Spain (Vallecillo et al 2008). …”
Section: Habitat Selection By Mediterranean Woodlarkssupporting
confidence: 65%
“…This is consistent with the intermediate disturbance hypothesis applied also at the landscape scale, which postulates that maximum diversity is provided by intermediate disturbance size, frequency and intensity (Roberts and Gilliam, 1995). Indeed, the rural land abandonment processes and the reduction in forestry activities due to the low profitability of traditional forest products and the introduction of new fuel sources have favoured forest maturation, increased biomass (Poyatos et al, 2003;Roura-Pascual et al, 2005;GilTena et al, 2009) and a potentially excessive landscape homogenization and densification that may induce the dominance of a few adapted species and may have a negative effect on some forest generalists or open habitat species (Vallecillo et al, 2008). For example, many forest bird species in the Mediterranean seem to be adapted to landscape heterogeneity derived from anthropogenic practices (Tellería andSantos, 1999), andLasanta-Martínez et al (2005) also observed a negative impact of abandoned rural landscapes and homogenization on biodiversity.…”
Section: The Relative Importance Of Landscape and Environmental Factomentioning
confidence: 99%
“…Forest bird species appear to benefit from forest maturation and spread, which has offset the potentially negative effects of fires on forest birds in Mediterranean regions (Preiss et al 1997;Moreira et al 2001;Suarez-Seoane et al 2002;Laiolo et al 2004;Sirami et al 2007;Gil-Tena et al 2009). Furthermore, once succession from shrubland to forest dominates over the creation of new low-vegetation areas derived from wildfire, open-habitat species might be the group most affected by losses of suitable habitat (Vallecillo et al 2007;De Cáceres et al 2013).…”
Section: Introductionmentioning
confidence: 99%